Numerical solution of boundary layer flow over a moving plate in a nanofluid with viscous dissipation: A revised model - Zulkifli, Siti Norfatihah; Md Sarif, Norhafizah; Salleh, M. Z. (Akademia Baru Publishing, 2019)
Model of boundary layer flow over a moving plate in nanofluid with viscous dissipation effect is revisited. A new boundary condition is applied with the assumption that there is no nanoparticle flux at the surface. The nanoparticle volume fraction on the boundary is passively control rather than active control and this makes the model more realistic. A similarity transformation is introduced to reduce the governing non-linear partial differential equation into ordinary differential equation. The ordinary differential equations are computed numerically through numerical method namely Runge-Kutta Felhberg (RKF) technique. Validations of the result has been made by comparing the present results with results from the previous studies. In this study, it is found that the presence of viscous dissipation contributes to an increase in temperature profile. In addition, it is observed that an increment in Brownian motion parameter produce negligible effect on temperature profile. Furthermore, both nanoparticle concentration and temperature profile intensify with an increase of thermophoresis parameter.